2003
DOI: 10.1021/jm021113r
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoline Binding Sites (IBS) Profile Modulation:  Key Role of the Bridge in Determining I1-IBS or I2-IBS Selectivity within a Series of 2-Phenoxymethylimidazoline Analogues

Abstract: The alpha- and beta-methyl derivatives of 2-phenylethylimidazoline (compounds 7 and 8) and the corresponding enantiomers were prepared and tested with the purpose of studying the role played by the ethylene bridge in modulating I(1)- and I(2)-IBS selectivity. The alpha-methylation appeared to be extremely critical regarding the affinity and selectivity for the I1-IBS subtypes (I1/I2 = 186 for imidazoline 7) and the stereospecificity of interaction (eudismic ratio (S)-(-)-7/(R)-(+)-7 = 5888). Instead, even if i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 48 publications
2
52
0
Order By: Relevance
“…In both cases, the presence of the methyl group in the bridge strongly disadvantaged the I 2 -IBS interaction. 13 Such observations suggested the existence of a "methyl pocket" in the α 2 -AR 17 and I 1 -IR, but not in the I 2 -IBS binding cavity. Compound 1 behaved as an antagonist at the three α 2 -AR subtypes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, the presence of the methyl group in the bridge strongly disadvantaged the I 2 -IBS interaction. 13 Such observations suggested the existence of a "methyl pocket" in the α 2 -AR 17 and I 1 -IR, but not in the I 2 -IBS binding cavity. Compound 1 behaved as an antagonist at the three α 2 -AR subtypes.…”
mentioning
confidence: 99%
“…Indeed, in in vivo studies, 3 displayed no cardiovascular effect and prevented the hypotensive and bradycardic action of clonidine. 13 The fact that several classes of substances, including those bearing an imidazoline ring, interact with α 2 -ARs and I 1 -IRs suggests that such systems might present analogies in the nature of some critical binding sites. 20 Based on this hypothesis, to modulate the biological profile of 3 from antagonism to agonism, recently, we prepared and studied its ortho phenyl derivative 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eudismic analysis (EA), in general, provides a valuable approach to elucidate the interaction between chiral compounds and their target proteins. 25,26 In addition, this analytical method is used in drug design and development to increase the selectivity and potency of chiral lead compounds toward their receptors. 27 In this study, the tools of EA were employed to identify the factors determining affinity and GlcA-transfer to edge closer to the mechanism of the UGT-catalyzed glucuronidation reaction at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…17−19 At low dose 1 also reduced hyperanxiety-like behavior after alcohol intoxication. 20 In contrast, the −CHCH− bridge induced efficacious I 1 -and I 2 -IBS recognition, as demonstrated by tracizoline (3) (pK i : I 1 -IBS 7.72, I 2 -IBS 8.72, α 2 -ARs < 6), 21 whereas the −NH− CH 2 − chain might be tolerated by ligands addressed to I 1 -, I 2 -IBS and α 2 -ARs, as reported for 4 (pK i : I 1 -IBS 9.30, I 2 -IBS 7.48, α 2 -ARs 7.14). 22,23 Our studies also indicated that the introduction of suitable decorations in the ortho position of the phenyl ring conferred to the ligand an interesting profile modulation from antagonism to agonism.…”
mentioning
confidence: 99%